PENGUKURAN USER EXPERIENCE APLIKASI MyIM3 DENGAN UEQ UNTUK MENYEDIAKAN SOLUSI PERBAIKAN LAYANAN - Laila, Anis Faizul Laila; Daniati, Erna Daniati (Prosiding Seminar Nasional Teknologi dan Sistem Informasi, 2025)
The development of digital technology has encouraged telecommunications service providers to introduce mobile applications that make it easier for users to access services independently. MyIM3 is one such application that provides features for purchasing credit, data packages, and account management. The success of an application is determined not only by the completeness of its features, but also by the user experience (UX), which influences customer satisfaction and loyalty. This study aims to evaluate the user experience of the MyIM3 application using the User Experience Questionnaire (UEQ) method, which measures six main dimensions: attractiveness, perpicuity, efficiency, dependability, stimulation, and novelty. The research instrument was a 26-item questionnaire distributed to 50 active MyIM3 user respondents. Data were analyzed quantitatively to obtain a comprehensive picture of user perceptions. The results show that the MyIM3 application is considered quite good in providing a user experience, although there are still aspects that need to be improved. These findings are expected to contribute to further research and provide input for the development of digital services.